2021
DOI: 10.1186/s12913-021-07041-8
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of COVID-19 lockdown for formal and informal resource utilization among home-dwelling people with dementia: results from the prospective PAN.DEM study

Abstract: Background COVID-19 isolated home-dwelling people with dementia (PwD) from home care services, respite care, and daytime activities. We aimed to investigate the consequences of these restrictions on informal (family, friends) and formal (homecare staff) resource utilization among co-residing (e.g., spouses) and visiting caregivers (e.g., children). Methods 105 PwD (≥65 years old) and their caregivers were included in the prospective PANdemic in DEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Research among informal caregivers of patients with dementia living at home in Norway, for example, also showed that almost 70% of relatives reported an increase in their care responsibilities [ 4 ]. The major staff shortages within HHC [ 17 ]—which were exacerbated further by the COVID-19 pandemic due to people’s fear of infection [ 3 ] and high rates of sick leave [ 18 ]—underline the importance of shifting services from HHC professionals to informal caregivers or encouraging clients to become more independent. However, the increase in the intensity of informal care provision also resulted in a higher burden for informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Research among informal caregivers of patients with dementia living at home in Norway, for example, also showed that almost 70% of relatives reported an increase in their care responsibilities [ 4 ]. The major staff shortages within HHC [ 17 ]—which were exacerbated further by the COVID-19 pandemic due to people’s fear of infection [ 3 ] and high rates of sick leave [ 18 ]—underline the importance of shifting services from HHC professionals to informal caregivers or encouraging clients to become more independent. However, the increase in the intensity of informal care provision also resulted in a higher burden for informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…We met COVID-19 related limitations in conducting this study. Due to the dramatically worsening care situation resulting in exacerbating BPSD and impinged trial protocol [ 23 , 53 , 54 ], we found it appropriate to solely analyze the prepandemic data from the first 6-month period despite compromising power and misbalancing group sizes (Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a national ICG survey in Norway, spouses/partners are among those who spend most hours on caregiving, and the perceived caregiver burden is associated with the extent of caregiving tasks [42]. During the COVID-19 pandemic, there was an increase in informal care, especially among ICGs who co-resided with the person with dementia [20]. There is also evidence that BPSD increased during the pandemic [21].…”
Section: Characteristics Of Icg Reporting and Not Reporting Abusive Actsmentioning
confidence: 99%
“…Because of the lockdown, many services for persons with dementia were reduced or canceled. A study from the first two months of lockdown in Norway found that formal care provided for persons with dementia on average decreased by 20.5 h per month, while informal care almost doubled [20]. Both the decrease in formal care and the increase in informal care were more pronounced when the ICG co-resided with the person with dementia.…”
Section: Introductionmentioning
confidence: 99%